Três Pavilhões de Sérgio Bernardes: Volta Redonda, Bruxelas e São Cristóvão. Contribuição à vanguarda arquitetônica moderna brasileira em meados do século 20. - Sombra Junior, Fausto Barreira (2020)
Erected in Ibirapuera Park, in the city of São Paulo, and opened to the public in February 1955, the still little known Volta Redonda Pavilion was conceived by the Carioca architect Sérgio Wladimir Bernardes at the request of Companhia Siderúrgica Nacional as promotional stand of then known the 1st International Fair of São Paulo, a event that was held during the celebrations of the fourth centenary of the city and that had the participation of large companies, a good number of nations and other important states of the Federation. This small bridge building, composed basically of profiles and other metallic elements, carries with it not only the inventiveness and important technical-ideological concepts present in the rich – and still little studied – trajectory of this professional, but also excerpts related to the constitution and consolidation of the capital of São Paulo, a city that in the then period sought to modernize through the development of its industrial park and the intense sociocultural effervescence process enjoyed. Immersed in this universe and based on the understanding of the architectural and/or artistic artefact capable of condensing and explaining program relations, composition, technique, materiality, environment etc., as well as the materialization of its own creative impetus, linked to aspects of collective longing in a given period, this thesis has as one of the main objectives to defend the contribution of the Volta Redonda Pavilion to the modern architectural avant-garde of São Paulo and from Brazil, for, even recognizing its value, few researchers devoted themselves to understanding it and correlating it, in greater depth, with the subsequent development of the work of its creator or even determining the possible reflexes of his contribution in his professional environment. Here it refers to the other two important pavilions conceived by Sérgio Bernardes in the same period: the award-winning Pavilion of Brazil at the Universal and International Exhibition of Brussels, from 1957 to 1958, and the Pavilion of the International Fair of Industry and Commerce, erected in São Cristóvão, Rio de Janeiro, between 1957-1960, projects that clearly hold the concepts and longings present both in their career, built in Ibirapuera Park, as well as in many other iconic buildings authored by this professional. In this sense, and focused on extensive analysis of primary sources – procedure based, among other methods, on the understanding of “indicdictory knowledge”, a term forged by the Italian historian Carlo Ginzburg – the work to be followed, structured from three different approximations (historical and contextual; descriptive and redesign; and analysis in the technical and ideological sphere), will seek to demonstrate the experimental character that characterized the extensive and polyphonic work of this intriguing architect and his dedication and increasing appeal to the improvement of the technique, the search for a certain industrialization and architectural inventiveness, qualities that, in the understanding of the present thesis, are fully crystallized in the three objects of study defined here.